PENGARUH KARTU BERGAMBAR TERHADAP KEMAMPUAN MEMBACA SISWA KELAS 1 SEKOLAH DASAR RAHVA MARENDAL 1 TAHUN PELAJARAN 2024-2025 - Priska Yolanda; Zaini Dahlan; Zunidar (PT. Hasba Edukasi Mandiri, 2025)
The number of students who are not yet fluent readers is the focus of this research. First-grade students at Rahva Marindal 1 Elementary School are the subjects of this study, which aims to document their reading comprehension during the 2024–2025 academic year. All twenty-eight first-grade students at Rahva Marindal 1 Elementary School during the 2024–2025 academic year constitute the population of this research. A software package called IBM SPSS Statistics 27 was used to assist with the data analysis process. The first-grade students at SD Marindal 1 showed improvement in their reading comprehension after using picture cards as a teaching aid. The asymp.sig (2-tailed) value was 0.000, as indicated by the